Aspects of Modernity in Ramkinkar’s Sculpture: A Study - Dr Ganesh Nandi (Innovative Research Thoughts, 2023)
Although there has always been a rich tradition in sculpture in India, Ramkinkar Baij has freed sculpture from the inertia of tradition. He created art by imbibing Eastern-Western art processes and drawing on his own life experiences. He has found a new way in every field of art-thought, subject, medium, technique, keeping in touch with the tradition. He created the first abstract sculpture in this country. He also created India's first environmental sculpture 'Sujata'. He paved the way for experimentation in sculpture by applying the readily available medium of cement-concrete and the throwing process. His work captures the extraordinary pace, rhythm, emotion, Indian way of life pulse and the magical play of light and shadow. He showed that sculptures were made without royal patronage. Showing deep compassion, made working people the subject matter of sculpture. Therefore, if judged as a whole, he is truly a modern sculptor in the Indian context. An attempt has been made in this study to analyze the nature of his modernism.